Assessment of an eye-tracking tool to discriminate between concussed and not concussed professional male rugby players: a cohort study - Brown, J.; Fuller, G. W.; McDonald, W.; Rasmussen, K.; Sawczuk, T.; Gilthorpe, M.; Jones, B.; Falvey, É. C. (The Physician and Sportsmedicine, 2025)
Objectives Concussion is a common injury in rugby union (`rugby`) and yet its diagnosis is reliant on clinical judgment. Oculomotor testing could provide an objective measure to assist with concussion diagnosis. NeuroFlex® evaluates oculomotor function using a virtual-reality headset. This study examined differences in NeuroFlex® performance in clinician-diagnosed concussed and not concussed elite male rugby players over three seasons.